The Role of Islamic Religiosity on the Relationship Between Risk, Trust, and Intention to Use Digital Payments During the COVID-19 Pandemic - Yudi Sutarso (International Journal of Islamic Economics and Finance (IJIEF), 2022)
There has been limited study on risk perception faced by digital payment customers, particularly during the COVID-19 pandemic, motivating this study to analyze the role of risk and trust on the intention and use of digital payments and confirm the moderating role of Islamic religiosity in the model. This study used the Partial Least Squares -Structural Equation Model (PLS-SEM) method, including a survey of 270 customers of three digital payment service providers: OVO, Gopay, and Dana. The key finding revealed that security and operational risks significantly impacted trust, even though they did not affect the intention to continue. Another significant result uncovered that Islamic religiosity moderated the effect of operational risk on trust. In this case, customers with a lesser religiosity level were more sensitive to the risk's impact. The significant contribution of this study is an expanding theory on the relationship between perceived risk, trust, and the use of digital payments. The study also offers recommendations to practitioners on managing risk and trust to increase the likelihood of using digital payment in the future. Furthermore, practitioners must consider religiosity regarding risk management, trust, and consumer protection.